ANALISIS NILAI-NILAI KEHIDUPAN PADA ANTOLOGI CERPEN: KOTA CERITA - Aprilya Siahaan; Odilia V. Simorangkir; Trisnawati Hutagalung (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this research is to analyze the values of life found in the short story anthology "Kota Cerita." The research type used in this study is descriptive research, which aims to collect information about the current state of a phenomenon. The study systematically describes written data in the form of words, sentences, and paragraphs that indicate the content of life values and the forms of conveying these values in "Kota Cerita." The research revealed that there are several life values in the short story collection, namely education, leadership, simplicity, mutual cooperation, sacrifice, morality, and courage. These values were found in specific stories within the collection, as indicated in the table provided